If it walks like Crohn's and talks like Crohn's, it must be…. (10th January 2013) - Hall, Philip S J; Allen, Patrick B; Diong, K L; Varghese, Abraham
Abstract : A 30-year-old man presented with a 6- month history of nausea, vomiting and diarrhoea. This was associated with 25 kg weight loss and a right-sided abdominal colic. He had been provisionally diagnosed with Crohn's disease 6 months back and treated with budesonide and mesalazine. Investigations including C reactive protein, white cell count, coeliac antibodies, fasting gut hormones and faecal elastase were all normal. Colonoscopy and ileoscopy were normal both macroscopically and microscopically. Small bowel series and labelled white cell scan were both unremarkable. A CT scan suggested the presence of mild right-sided abdominal lymphadenopathy. Laparoscopy of entire small bowel and colon was normal. But had something been missed? An adrenocorticotrophic hormone stimulation test demonstrated inadequate cortisol response and a diagnosis of adrenal insufficiency was confirmed. Addison's disease can present with a variety of gastrointestinal symptoms and should be considered in the diagnostic work-up of these patients.